Membaca Perempuan dalam Hadis Misoginis: Usaha Kontekstualisasi Nilai Kemanusiaan - Mohamad Muhtador (UIN Raden Mas Said Surakarta, 2017)
Gender reading of misogynist hadiths in this case is aimed at uncovering models of understanding of the traditions of gender-biased prophets, the article not least of the prophetic traditions circulating in society with the style and expression of hatred against women. This has a negative impact on the potential development of women and the existence of sex. Therefore, in this position, the study of gender becomes very urgent to open the variety of understanding with different styles as an attempt to obtain justice and give a new color in understanding, so that interpretation does not become a single truth in understanding the teachings of religion, especially related to the hadith of the Prophet. The results of this study indicate that the gender relations in misogynical hadiths are an attempt to reread with a gender perspective that is more concerned with moral ideals in exploring the traditions of the Prophet, specifically with misogynist hadiths.